2019
DOI: 10.2351/1.5096100
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ultrasonic amplitude and position in the vibration distribution on the microstructure of a laser beam welded aluminum alloy

Abstract: There are many reasons for influencing the laser beam induced weld pool. The manipulation of the dynamics, the solidification, the resulting grain size, and in the end, as a result of the aforementioned influencing, the mechanical characteristics of the weld is the aim of different attempts to gain an impact on the melt. Aluminum alloys tend to porosity formation because of different solubility of hydrogen in solid and liquid states. For reliable welds, the porosity has to be limited. An ultrasound excitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Metals 2020, 10, x FOR PEER REVIEW 5 of 13 Table 3), for an ultrasonic amplitude of 6 µm only one welding test per wave position is conducted for testing the effects of excessive excitation, which effects spatter. The applied parameters were determined by previous experiments [4,12]. Metallographic cross sections of each specimen are prepared.…”
Section: Weld Appearancementioning
confidence: 99%
See 2 more Smart Citations
“…Metals 2020, 10, x FOR PEER REVIEW 5 of 13 Table 3), for an ultrasonic amplitude of 6 µm only one welding test per wave position is conducted for testing the effects of excessive excitation, which effects spatter. The applied parameters were determined by previous experiments [4,12]. Metallographic cross sections of each specimen are prepared.…”
Section: Weld Appearancementioning
confidence: 99%
“…Hence, it can prevent segregation including its consequences and foster a finer grain structure, because dendrites break through mixing, which in turn creates more nucleation sites [3]. A finer grain structure improves strength as well as ductility and hardness [4]. In addition, porosity and hardness in the heat affected zone can be decreased and penetration depth can be increased for aluminium welds [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that grain refinement is caused by dendrite fragmentation. The influence of the ultrasonic amplitude on the weld seam properties has been investigated in [6]. The extent to which local excitation influences the weld seam was also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The local excitation depends on the excited vibration shape of the system and, in particular, on the relative position of the weld with respect to the vibration nodes and antinodes of the system. In [6], the situation where the melt bath is in a vibration anti-node (which means that the entire melt bath is shaken) was compared with the situation where the melt bath is in a vibration node (which means that the borders of the melt bath are expanded and compressed). The ultrasonic frequency used was 20 kHz.…”
Section: Introductionmentioning
confidence: 99%